ANALISIS WACANA KRITIS TERJEMAHAN AL-QUR’AN ARTHUR JOHN ARBERRY - M. Riyan Hidayat; Muhafizah Muhafizah; Aty Munshihah (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2022)
Abstract The translation of the Koran by orientalists often gets a negative response. However, Arberry's translation of the Koran as part of the orientalists countered the corrupted image through his work. This acceptance of his work wants the author to express through Van Dijk's critical discourse analysis approach which focuses on text, social cognition and social context. The results of this study indicate that Arberry sees the Qur'an as a supernatural work that must be interpreted in an original way. In social cognition, Arberry was also influenced by the great concept of Reynold Alleyne Nicholson for his anxiety about the translation of the Qur'an. Meanwhile, in the social context, Arberry's life journey began with his desire to translate the Qur'an objectively.